Pengaruh Kualitas Produk, Brand Image, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada e_Commerce Lazada (Studi Kasus Mahasiswa FEB Unisma Angkatan 2018) - Heriyanto Heriyanto; Muhammad Ridwan Basalamah; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of product quality, brand image, price and service quality on consumer satisfaction at Lazada e_commerce (Case Study of FEB Unisma Students Forces 2018). The variables used in this study are. Consumer satisfaction variable (dependent variable), while the independent variables are product quality, brand image, price and service quality.The results of this study partially concluded that the product quality variable, price had a significant effect on consumer satisfaction, while brand image and service quality had no significant effect on consumer satisfaction and simultaneously concluded that there was an influence between product quality, brand image, price and service quality variables on satisfaction. consumer. Keywords: Product Quality, Brand Image, Price, Service Quality, Consumer Satisfaction